Recent advances in the mechanisms and rehabilitation strategies of exercise interventions for osteoporosis in older adult women - Zheng, Bing; Chen, Jing; Li, Yiheng (Frontiers in Physiology, 2025)
Osteoporosis is a prevalent musculoskeletal disorder among older adult women, characterized by reduced bone mass and deterioration of bone microarchitecture, leading to decreased quality of life and increased fracture risk. This review summarizes recent advances in the research on exercise interventions for the prevention and treatment of osteoporosis in this population. The mechanisms by which exercise exerts beneficial effects include mechanical stimulation that enhances osteoblast activity, hormonal regulation to maintain bone metabolic balance, improved skeletal blood circulation, and increased muscle strength and postural stability. Various forms of exercise demonstrate distinct therapeutic effects: aerobic exercise enhances bone strength through regular loading stimuli; resistance training directly stimulates bone formation; balance and flexibility training improve coordination and reduce the risk of falls; and emerging modalities such as whole-body vibration have shown potential benefits for bone health. The development of exercise prescriptions should be tailored to the individual’s physical condition, incorporating appropriate types, intensities, durations, and frequencies of exercise, with an emphasis on pre-exercise health assessments and safety monitoring throughout the intervention. Although the efficacy of exercise interventions is widely recognized, current research still faces limitations in areas such as personalized program design, synergistic effects of different exercise modalities, and strategies to improve long-term adherence. Further studies are warranted to optimize clinical application.